Ecological and Environmental Study of Eupatorium adenophorum Sprengel (Banmara) with Reference to its Gall Formation in Gorkha-Langtang Route, Nepal - Shrestha, Keshav; Wilson, Emma; Gay, Honer (Journal of Natural History Museum, 2009)
Eupatorium adenophorum Sprengel is a forest killer widely spreading as weed in Nepal. A study on its ecology and utilization was carried out in central Nepal with reference to its gall formation. This banmara is attacked by Procecidochares utilis, a gall which causes metabolic and physical damage to the plant. The main field survey was done in Gorkha-Langtang area and compared with the phenomenon with that of Kathmandu Valley. It has been found that the index of exposure has no effect on the plant growth; pH also has no effect where as soil and gall formation has some effect on plant growth. Artemisia vulgaris and Urtica dioca were commonly found in association with Eupatorium adenophorum. Though the plant acts as forest killer, some beneficial phenomena were also recorded. Key words: Correlation coefficient; Gall formation; index of exposure; life cycle; quadrates Journal of Natural History Museum Vol. 23, 2008 Page 108-124